2019
DOI: 10.36929/jpk.v7i2.132
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Faktor Yang Berhubungan Dengan Kepatuhan Diet Penderita Diabetes Melitus

Abstract: Kepatuhan pengobatan penderitan Diabetes Melitus merupakan suatu perilaku pasien dalam menjalani pengobatan, mengikuti diet, atau mengikuti perubahan gaya hidup lainnya sesuai dengan anjuran medis dan kesehatan. Tujuan penelitian ini adalah untuk mengetahui mengetahui analisis faktor yang berhubungan dengan kepatuhan diet Penderita Diabetes Melitus di wilayah kerja Puskesmas Harapan Raya. Rancangan penelitian ini menggunakan pendekatan analisis uji statistik uji regeresi logistik berganda dengan sampel yang di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
2
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 0 publications
2
2
1
2
Order By: Relevance
“…In line with this theory, research regarding the factors that influence diet adherence in T2DM patients at the Kedungmundu Public Health Center in Semarang City shows that there is a relationship between education level and adherence to diet in T2DM patients as evidenced by the results of the chi-square test obtained p = 0.046 [19]. However, several studies also showed results consistent with this study, which showed no significant relationship between education level and patient dietary adherence [20,21,22]. Formal education may shape a person's health behavior, but other factors besides the level of education also play a role in patient dietary adherence.…”
Section: Resultssupporting
confidence: 73%
“…In line with this theory, research regarding the factors that influence diet adherence in T2DM patients at the Kedungmundu Public Health Center in Semarang City shows that there is a relationship between education level and adherence to diet in T2DM patients as evidenced by the results of the chi-square test obtained p = 0.046 [19]. However, several studies also showed results consistent with this study, which showed no significant relationship between education level and patient dietary adherence [20,21,22]. Formal education may shape a person's health behavior, but other factors besides the level of education also play a role in patient dietary adherence.…”
Section: Resultssupporting
confidence: 73%
“…This results in these patients tend to be disobedient (Anisa & Bahri, 2017). Another study that supports the results of this study is the research conducted by (Rohani & Ardenny, 2019) which shows that patients who have experienced a disease for one to five years tend to be more obedient to the process of taking drugs and recommendations given by doctors because of their great curiosity. and the desire to recover is great, while patients who have experienced the disease for more than five years have a tendency to have poorer adherence to taking medication and adherence to doctor's recommendations.…”
Section: Identify Hypertension Diet Compliance Before Virtual Assista...supporting
confidence: 77%
“…Based on the general data of respondents, it is known that most of the respondents (53.6%) are 31-40 years old. One of the factors that influence the compliance of hypertension patients is age (Rohani & Ardenny, 2019). A person's compliance depends on age where at the age of 31 to 40 years the individual already has a broader insight so that a person can do what is good for himself, including adherence to a diet (Anisa & Bahri, 2017).…”
Section: Identify Hypertension Diet Compliance Before Virtual Assista...mentioning
confidence: 99%
“…In contrast to Ruiz-Roso et al, (2020)'s study, the majority of persons with T2DM were obese (63%). The optimal management of T2DM, particularly during the Covid-19 pandemic, is emphasized through the management of modifiable factors, particularly living a healthy lifestyle that includes efforts to achieve and maintain normal nutritional status to prevent obesity, apply a balanced diet based on nutrition principles, and engage in regular physical activity according to age (Rohani & Ardenny, 2019). Vitamin C intake in T2DM patients was divided into three categories: less (43.8%), good (36.2%), and more (20%).…”
Section: Resultsmentioning
confidence: 99%